2011
DOI: 10.1111/j.1553-2712.2011.01121.x
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence-based Diagnostics: Adult Septic Arthritis

Abstract: Background Acutely swollen or painful joints are common complaints in the emergency department (ED). Septic arthritis in adults is a challenging diagnosis, but prompt differentiation of a bacterial etiology is crucial to minimize morbidity and mortality. Objectives The objective was to perform a systematic review describing the diagnostic characteristics of history, physical examination, and bedside laboratory tests for nongonococcal septic arthritis. A secondary objective was to quantify test and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
214
1
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(234 citation statements)
references
References 83 publications
3
214
1
16
Order By: Relevance
“…Papanicolas et al identified a CRP >100 mg/l as predictive of septic arthritis with a sensitivity of 86 %, but a low specificity of 48 % [20]. Other reports challenged the predictive value of serum inflammatory markers for the diagnosis of septic arthritis [7]. While our study detected a significant association of a CRP value above 150 mg/l as "predictive" in multivariate analysis, the corresponding ROC curve was moderate at best.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Papanicolas et al identified a CRP >100 mg/l as predictive of septic arthritis with a sensitivity of 86 %, but a low specificity of 48 % [20]. Other reports challenged the predictive value of serum inflammatory markers for the diagnosis of septic arthritis [7]. While our study detected a significant association of a CRP value above 150 mg/l as "predictive" in multivariate analysis, the corresponding ROC curve was moderate at best.…”
Section: Discussioncontrasting
confidence: 54%
“…In the literature, the overall sensitivity ranges between 30 and 60 % [1,3,7], whereas for prosthetic joint infections, Morgan et al identified a 27 % sensitivity of intraoperative Gram staining [17], while the value of inflammatory markers for predicting culture-positive arthritis was less convincing. Several studies mentioned a positive association between occurrence of septic arthritis and elevated serum CRP levels [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since their inception, these risk factors have been used as a tool to guide management with hip aspiration and synovial fluid analysis in cases when multiple risk factors are present. After an aspiration has been performed, it has generally been accepted that a synovial white cell count greater than 100,000 cells/mm 3 likely [3] represents a septic hip requiring surgical management. Values between 25,000 and 75,000 cells/mm 3 represent a Bgray zone^where professional opinion and management differs among treating physicians.…”
Section: Introductionmentioning
confidence: 99%